Nilai Konseling Islam pada Budaya Wetu Telu di Kabupaten Lombok Utara - Rahmad Hidayat; Mohamat Hadori (Fakultas Dakwah Universitas Ibrahimy, 2021)
Humans as social beings, of course, need and care for each other in order to live peacefully in their relationship with God, fellow humans and nature. As well as the relationship of religion and culture that are both attached to a person. The purpose of this study was to describe the value of Islamic counseling in the Wetu Telu Culture. To obtain comprehensive information and data, this research uses an ethnographic type of research. The results of the study show that: First, there is an attitude of tolerance that makes people understand each other, appreciate, and understand anything that is done by people who are not of the same belief or descent. Second, the attitude of caring for the environment such as forests and animals which are very well guarded by customs so that they remain sustainable. Good relations are established between fellow Wetu Telu adherents by helping each other, visiting, appreciating and respecting each other, and not only with the Wetu Telu group but also with the newcomers who despite having different beliefs between them